Perception and Current Use of E-cigarettes Among Youth in China - Xiao, Lin (Nicotine Tob Res, 2018)
INTRODUCTION: This study provides nationally representative estimates of electronic cigarette (e-cigarette) use among youth in China and explores the factors associated with awareness and use of e-cigarettes and the relationship between e-cigarette and conventional tobacco use. METHODS: This study examined data from the Global Youth Tobacco Survey, which was completed by 155 117 middle school students (51.8% boys and 48.2% girls) in China, and employed a multistage stratified cluster sampling design. For data analysis, SAS 9.3 complex survey procedures were used, and logistic regression was used to explore factors associated with e-cigarette use and the relationship between e-cigarette and conventional tobacco use. RESULTS: About 45.0% of middle school students had heard of e-cigarettes, but only 1.2% reported using e-cigarettes in the last 30 days. Among never-smokers, e-cigarette users were more likely to intend to use a tobacco product in the next 12 months than nonusers (adjusted odds ratio [OR] = 6.970, 95% confidence interval [CI] = 4.474% to 10.857%), and more likely to say that they would enjoy smoking a cigarette (adjusted OR = 14.633, 95% CI = 11.328% to 18.902%). E-cigarette use was associated with previous experimentation with cigarette smoking (OR = 3.2), having noticed tobacco advertising in the past 30 days (OR = 2.7), having close friends who smoke (OR = 1.4), and thinking tobacco helps people feel more comfortable in social situations (OR = 3.3) and makes young people look more attractive (OR = 1.3). CONCLUSIONS: E-cigarette use among youth in China remains low but awareness is high. E-cigarette use was associated with increased intentions to use tobacco. Enhanced prevention efforts are needed targeting e-cigarette use among youth. IMPLICATIONS: This study is the first nationally representative survey of e-cigarette use among youth in China. It found that among middle school students, prevalence of e-cigarette use is 1.2% and prevalence of e-cigarette awareness is 45.0%. Chinese youths use e-cigarettes as a tobacco product rather than an aid to quitting. Among never-smokers, e-cigarette users were more likely to have intentions to use a tobacco product in the next 12 months, more likely to use a tobacco product offered by their best friends and enjoy smoking a cigarette than nonusers.